Ultrasonographic evaluation of testicular and Pampiniform plexus characteristics in young bulls under different microclimatic conditions in a tropical environment - Joedson Dantas Gonçalves; Alexandre Rossetto Garcia; Rubens Paes de Arruda; José Ricardo Macedo Pezzopane; Felipe Tonato; Alda Juliana Castro de Sousa; Lívia Ferreira Pinho; Veronica Schinaider do Amaral Pereira; Gabriel Brun Vergani; Maria Emilia Franco Oliveira (Scientific Reports)
Abstract This study aimed to evaluate the ultrasonographic characteristics of the testicles and pampiniform plexus of young bulls from 8 to 19 months of age under different microclimatic conditions. For this, 46 animals (8.0 ± 0.5 months and 211.0 ± 5.9 kg) were raised in two intensive rotational systems for 12 months, in which 24 animals (Nelore, n = 12; Canchim, n = 12) in a silvopastoral system and 22 animals (Nelore, n = 10; Canchim, n = 12) in a non-shaded pastoral system. Testicular biometric measurements, B-mode ultrasound assessments (echogenicity and heterogeneity of the testicular parenchyma and mediastinum), color Doppler (blood perfusion of the testicular parenchyma and pampiniform plexus), spectral Doppler of the supratesticular artery (pulsatility and resistance index), and blood collection from the jugular to determine testosterone concentration were performed monthly. Data were analyzed using the PROC MIXED procedure of SAS (p < 0.05), and possible interactions between production systems and animal age are presented. There was no difference in testicular volume variables (p = 0.4) between production systems over time. For parenchymal echogenicity (p = 0.3), a progressive increase was observed over time, with a maximum peak at 12 months of age, but without difference between systems. For the relative Doppler area of the testicular parenchyma (p = 0.4) and plexus (p = 0.1), values were decreased at 16 months of age, but without a difference between systems. For the velocimetric indices of the supratesticular artery, there were decreases in the pulsatility index (p = 0.3) and resistance index (p = 0.04), with no difference between the production systems. In conclusion, the variations observed in the present study are more related to age. Thus, there are no differences in the characteristics observed by ultrasound in young bulls kept in different microclimatic conditions under the circumstances studied.